How the lived experiences of black women can be understood through devised theatre informed by psychophysical actor training: an adaptation of the Tadashi Suzuki actor training technique - Makgabutlane,Linda (Department of Drama, 2022)
In this study I aim to use my body as a tool to derive themes for use in performance making and to underpin this in theory. I focus on aspects of Tadashi Suzuki (1986) actor training (referred to as Suzuki training), free writing and the body. I use black feminism, cognitive neuroscience and body theory to account for my lived body, which I then use in performance. Practice and theory informed each other in a cyclical manner in accordance with Practice as Research as a methodology. Therefore, elements that emerged from my practice determined the theory included in the study, as practice was considered a way of knowing. I work to establish a relationship between race, subjugation and some of the multiple implications thereof on the body in the urban context: I draw on limited notions of culture and the body to interrogate how these can materialise in performance. The study also addresses aspects of the performing body to support why I derive value in Suzuki (1986) training as one psychophysical actor training tool. I theoretically discuss this technique as developing expressive abilities in young performers. The primary purpose of this research is to create work that is rooted in the tradition of devising. My research moves between the physical body and the body in performance in a South African context as I worked to conceptually account for the body in both instances. Although limited, this research includes theories that account for the performing body engaged in somatic foot-based practices where these interact with my practice. I further discuss the devising process I undertook with a cast, as a performance maker, my findings and reflection on this process.